Self‐reported word‐finding complaints are associated with cerebrospinal fluid amyloid beta and atrophy in cognitively normal older adults. Issue 1 (9th February 2022) - Montembeault, Maxime; Stijelja, Stefan; Brambati, Simona M.
Abstract: Introduction: Self‐reported word‐finding difficulties are among the most frequent complaints in cognitively normal (CN) older adults. However, the clinical significance is still debated. Methods: We selected 239 CN from the Alzheimer's Disease Neuroimaging Initiative database who had completed the Everyday Cognition (ECog) questionnaire, as well as a lumbar puncture for amyloid beta (Aβ) and magnetic resonance imaging. Results: Word‐finding complaints, with a few other memory items, were significantly more severe compared to all other cognitive complaints. Ecog‐Lang1 (Forgetting names of objects) severity significantly predicted Aβ levels in CN, even when controlling for general cognitive complaint, demographic, and psychological variables. Individuals with high Ecog‐Lang1 complaints showed atrophy in the left fusiform gyrus and the left rolandic operculum compared to CN with low complaints. Discussion: Overall, our results support the fact that word‐finding complaints should be taken seriously. They have the potential to identify CN at risk of AD and support the need to include other cognitive domains in the investigation of subjective cognitive decline.